2012 Great Plains drought not caused by climate change. (10th September 2013) - Schultz, Colin
Abstract : From May to July 2012, the Great Plains region of the western United States faced a powerful and unpredicted drought. Following 7 months of normal rainfall, the drought was one of the largest deviations from seasonal precipitation rates seen in the region since observations began in 1895. When such extreme events take place today against the backdrop of ongoing global climate change, they raise questions about the relationship between climate change and natural disasters.